Pendekatan Historis dalam Studi Islam: Analisis Konseptual, Metodologis, dan Implementatif - Diva Prima Aisyahrani; Sembodo Ardi Widodo; Yusuf Hulwani (Lembaga Yasin AlSys, 2026)
Although the historical approach in Islamic studies has been addressed in a number of scholarly works, studies that integrate its conceptual, methodological, and implementative dimensions within a single analytical framework remain limited. This study aims to analyze the epistemological nature, urgency, operational stages, functions, strengths and limitations, and application of the historical approach in Islamic studies, with particular attention to contemporary challenges in Indonesia. This study used a qualitative library research method by relying on scholarly literature from the last decade as the source of review. The data were analyzed through conceptual review and critical synthesis of relevant literature to formulate the relationship between normativity, historicity, and operational methodology in Islamic studies. The results show that the historical approach functions not only reconstructively but also critically and transformatively in understanding Islamic teachings contextually. Through the stages of heuristics, verification, interpretation, and historiography conducted systematically, this approach is able to produce a more objective and nuanced understanding of religious texts and practices. This review also shows that the historical approach is important for avoiding literalist readings of the Qur’an, tracing the Islamization process of Nusantara, and interpreting local religious traditions such as kenduri. The novelty of this study lies in its integrative synthesis that bridges the normativity-historicity framework with operational methodology, thereby filling a gap in the literature that has tended to discuss these aspects separately. This study contributes to the development of methodological studies in Islamic studies and provides implications for academics and researchers in applying the historical approach critically, contextually, and systematically in understanding the dynamics of Islamic teachings and practices.